Transition in offences of not paying maintenance in Poland: Przemiany przestępstwa niealimentacji w Polsce (Archives of Criminology, 2023)
How can the courts ensure someone pays maintenance? What is a sufficient and just reaction to avoiding these obligations? Non-payment of maintenance is an offence in most, but not all, European countries. Due to an amendment in the Polish Penal Code of 23 March 2017, the scope of the criminalisation of this offence in Poland expanded significantly. This paper presents a statistical analysis on this specific type of crime 30 years before and 30 years after the socio-political transformation in Poland and discusses the methods and purpose of criminal justice responses to this issue.